Hydrogeology of Karang Mumus Watershed in Samarinda, East Kalimantan Province, Indonesia - Shalaho Dina Devy (Universitas Muhammadiyah Surakarta, 2018)
Samarinda is part of an anticlinorium, which is marked by the existence of many anticlines. In addition, various types of rock and aquifer can be found in the city due to the uniqueness of geological structure of the area. Nevertheless, the literature are lacking attention of hydrogeological condition of this area. This research aims to determine the hydrogeology of the Karang Mumus watershed, particularly in relation to its geology and land use conditions. The research uses an inductive method, with an analytical approach consisting of a study of the land use, hydrological conditions, geology, geomorphology and hydrogeology. The Karang Mumus watershed can be divided into three hydrogeological layers: (1) an aquitard layer, the top layer, which has a hydraulic conductivity of 4.3 × 10-6 m/sec, and is dominated by siltstone; (2) an aquifer layer in the middle, with a hydraulic conductivity of 2.6 × 10-4 m/sec, dominated by sand and sandstone; and (3) an aquiclude layer occupying the lower layer, with a hydraulic conductivity of 1.6 × 10-11 m/sec, and which is dominated by claystone.